Rapid detection and differentiation of avian infectious bronchitis virus: an application of Mass genotype by melting temperature analysis in RT-qPCR using SYBR Green I - Okino, Cintia Hiromi [UNESP]; Silva Montassier, Maria de Fatima [UNESP]; Oliveira, Andressa Peres de [UNESP]; Montassier, Helio Jose [UNESP] (Japan Soc Vet Sci, 2018)
A method based on Melting Temperature analysis of Hypervariable regions (HVR) of S1 gene within a RT-qPCR was developed to detect different genotypes of avian infectious bronchitis virus (IBV) and identify the Mass genotype. The method was able to rapidly identify the Mass genotype among IBV field isolates, vaccine attenuated strains and reference M41 strain in allantoic liquid and also directly in tissues. The RT-qPCR developed detected the virus in both tracheal and pulmonary samples from M41-infected or H120-infected birds, in a larger post-infection period compared to detection by standard method of virus isolation. RT-qPCR method tested provided a sensitivity and rapid approach for screening on IBV detection and Mass genotyping from IBV isolates.
Keywords: avian infectious bronchitis virus; Massachusetts; melting temperature analysis; RT-qPCR; S1 gene